Comparative genomics of Leishmania donovani progeny from genetic crosses in two sand fly species and impact on the diversity of diagnostic and vaccine candidates. - Jovana Sádlová; Matthew Yeo; David S Mateus; Jody Phelan; Le Anh Hai; Tapan Bhattacharyya; Stefan Kurtev; Ondrej Sebesta; Jitka Myskova; Veronika Seblova; Björn Andersson; Paola Florez de Sessions; et al. (Public Library of Science (PLoS), 2024)
Sand fly transmitted Leishmania species are responsible for severe, wide ranging, visceral and cutaneous leishmaniases. Genetic exchange can occur among natural Leishmania populations and hybrids can now be produced experimentally, with limitations. Feeding Phlebotomus orientalis or Phlebotomus argentipes on two strains of Leishmania donovani yielded hybrid progeny, selected using double drug resistance and fluorescence markers. Fluorescence activated cell sorting of cultured clones derived from these hybrids indicated diploid progeny. Multilocus sequence typing of the clones showed hybridisation and nuclear heterozygosity, although with inheritance of single haplotypes in a kinetoplastid target. Comparative genomics showed diversity of clonal progeny between single chromosomes, and extraordinary heterozygosity across all 36 chromosomes. Diversity between progeny was seen for the HASPB antigen, which has been noted previously as having implications for design of a therapeutic vaccine. Genomic diversity seen among Leishmania strains and hybrid progeny is of great importance in understanding the epidemiology and control of leishmaniasis. As an outcome of this study we strongly recommend that wider biological archives of different Leishmania species from endemic regions should be established and made available for comparative genomics. However, in parallel, performance of genetic crosses and genomic comparisons should give fundamental insight into the specificity, diversity and limitations of candidate diagnostics, vaccines and drugs, for targeted control of leishmaniasis.